Patterns of care and outcome of CIC‐rearranged sarcoma patients: A nationwide study of the French sarcoma group. (20th December 2022) - Brahmi, Mehdi; Gaspar, Nathalie; Gantzer, Justine; Toulmonde, Maud; Boudou‐Rouquette, Pascaline; Bompas, emmanuelle; Firmin, Nelly; Valentin, Thibaud; Cancel, Mathilde; Duffaud, Florence; Bertucci, Francois; Perrin, Christophe; et al.
Abstract: Background: CIC‐ rearranged sarcomas ( CIC ‐RS) represent the most frequent subset of "Ewing‐like" undifferentiated small round cell sarcomas. These tumors tend to be more aggressive than Ewing sarcomas. Moreover, treatment strategy can differ according to teams. The primary aim of this retrospective study was to describe the characteristics, treatments, and outcome for patients with CIC ‐RS included in the French NETSARC+ database. Methods: Pediatric and adult patients from 13 French centers with a diagnosis of CIC ‐RS were registered from October 2008 to March 2021. Patients and tumors characteristics were collected from the national network NETSARC+ database (http://netsarc.sarcomabcb.org ). CIC ‐RS diagnosis was pathologically and molecularly confirmed with a central review by expert pathologists. Two groups of patients were studied: those treated as classical Ewing sarcomas (cohort EwS) and those treated as high‐grade soft tissue sarcomas (cohort STS) according to ESMO and/or EpSSG guidelines. Survival was calculated using the Kaplan–Meier method and the log‐rank test was used to compare survival. Results: Among 79 patients, the male/female sex ratio was 0.7 and the median age at diagnosis was 27 years (range 2–87). With a median follow‐up of 37 months, 39 patients died of the disease. Median overall survival from diagnosis was 18 months, with no significant difference between both cohorts ( p  = 0.9). Nevertheless, when focusing on patients with metastatic disease at diagnosis ( N  = 21), all patients from cohort STS died of disease while some patients from cohort EwS were still alive and in complete remission. Conclusion: FSG experience confirms the aggressive clinical course of CDS patients regardless of chemotherapy regimen. Abstract : Two groups characterized by different patterns of care were evaluated in our study. On one hand (cohort 1), patients were treated as Ewing sarcomas, and on the other hand (cohort 2), patients were treated as high‐grade soft tissue sarcomas. Overall, the prognosis was poor and there were no statistical differences in overall survival and relapse‐free survival between the two groups. Nevertheless, a significant proportion of patients with metastatic CDS from cohort 1 achieved very long‐term survival and might be cured.